The position of Slovakia in competitiveness ranking – the causes, impacts and prospects - Stredná, Lucia; Zúbková, Mária (Business, Management and Economics Engineering, 2012)
A country’s competitiveness could be translated as its ability to successfully compete within international comparison also as a prosperity which is expressed by productivity growth of economy and living standards. Is Slovakia competitive? What are its strengths and weaknesses? What are the leading countries of the European Union in competitiveness ranking? In what aspects is Slovakia falling behind countries of V4? Strengthening of which competitive advantages is perspective for the Slovak Republic? We will try to find answers to these questions in an analysis of competitiveness based on the Global Competitiveness Reports. This thesis focuses on definition of the competitiveness in general, apprises of measuring methodology based on multicriterial evaluation and summarises pros and cons of this benchmark. The main focus is on the Slovak Republic and its position in the international ranking. In detail we will focus on comparison of the Slovak Republic with countries of V4 region. It is the authors’ ambition to bring critical view on position of the Slovak Republic in the international comparison and to formulate recommendations for the future that could contribute to strengthening of competitiveness and success of our country.